PENGARUH MOTIVASI DAN PENGETAHUAN PRODUK PERBANKAN SYARIAH TERHADAP KEPUTUSAN MENJADI NASABAH BANK SYARIAH INDONESIA (Studi Kasus Ex Bank Syariah Mandiri KCP Palembang KM 6) - Erinda Resti; Havis Aravik; Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
This study discusses the influence of motivation and knowledge of Islamic banking products on the decision to become a customer of Bank Syariah Indonesia (Case Study of Ex Bank Syariah Mandiri Kcp Palembang Km 6). Descriptive quantitative research method, with a population of 3,612 customers and 97 samples. While the data collection technique using questionnaires and documentation and data analysis is multiple linear regression analysis. The results obtained show that the motivation to avoid usury and knowledge of Islamic banking products simultaneously on the decision to become a customer has a positive and significant effect with the proportion of motivation to avoid usury (X1) and knowledge of Islamic banking products (X2) on the decision to become a customer (Y) of 75 ,2%. Meanwhile, for the partial test of the motivation to avoid usury and knowledge of Islamic banking products on the decision to become a customer, it is known that the motivation to avoid usury (X1) has a positive and significant effect. The second variable knowledge of Islamic banking products (X2) also has a positive and significant effect on the decision to become a customer (Y) at Bank Syariah Indonesia (Ex. Bank Syariah Mandiri KCP Palembang KM 6).